Mapping Political Violence in a Globalized World: The Case of Hindu Nationalism - Kamet, Sangeeta (Social justice, 2003)
Part of a special section on the intersection of ideologies of violence. An examination of the ideological basis of new and extreme forms of violence against minorities in India, especially against Muslims, and of the support for such violence from the Indian community in the U.S., is presented. In particular, the horrific carnage in the western state of Gujarat in 2002 is considered, to demonstrate the ideology of the Hindu nationalist movement that makes such violence possible. In addition, the Indian-American community's investment, both material and ideological, in furthering the Hindu nationalist movement's cause is outlined.